Thauma e pensar bem na educação infantil - Marcos Antônio Lorieri; Eduardo Gasperoni de Oliveira (EccoS – Revista Científica)
The text is the result of a research whose theme was: Philosophy and Education to Think Well in Early Childhood Education, which focused on the possible contributions of the proposal of the Philosophy Program for Children-Education for the Thinking of Matthew Lipman for the establishment of pedagogical procedures that favor the maintenance and development of the natural curiosity of the children around the know. In Childhood Education, there is usually no concern and procedures aimed at nourishing this natural curiosity manifested by the expressions of admiration and astonishment (thauma, as Plato and Aristotle defined it) of children, a curiosity that drives the search for explanations and understandings. The central question here is: to what extent do initial reflective practices based on children's questions, as proposed by Lipman, contribute to an education for thinking well in Early Childhood Education? The text presents considerations and propositions regarding what can be done in Early Childhood Education. The main theoretical reference is Lipman's ideas plus those of other thinkers such as Paulo Freire, Karl Jaspers, Hannah Arendt, Darcísio Muraro and John Dewey. It is a bibliographical research that uses as analytical categories: children's curiosity (thauma), think well, dialogue and education to think well.